Posters against the Patriarchy: Violence across the Public/Private Binary in Brussels - Schoonheim, Liesbeth (HannahArendt.net, 2024)
Street protests create spaces of appearance (Arendt) that galvanize public support for fighting hitherto hidden forms of precarity and oppression. Put in these terms, street protests raise questions about their duration, as they rely on the physical proximity of people; they also raise concerns about who can and cannot participate in this space of appearance and in what way, as public space is subject to various forms of policing (Butler). In this paper, I investigate these limits of embodied resistance by looking at a different form of street protest, namely the feminist collectives that put up posters in the streets of Brussels denouncing gender- and sex-based violence. Some of these focus on feminicide, publishing the name of victims of domestic violence, while others target street harassment by imploring passers-by to “laisse[r] les filles tranquilles” and yet other denounce everyday sexism. In different ways, these interventions relate isolated and privatized experiences of violence to patriarchal structures. While these interventions preceded the COVID-19 lockdowns, the rigid enforcement of the public-private divide during the pandemic underlined their importance. In this paper, I use the public-private distinction as a hereustic device to argue that these various posters taken together provide a cartography of heteropatriarchal violence (Gago). In the first two sections, I start from the observation that these artefacts are intended as a (semi-)permanent mark on the public space; and they invoke those who face various forms of gender- and sex-based violence, reclaiming the streets as a site of commemoration, refusal and of free movement. I argue that these collectives operate as a swarm (Gago, Connolly): they operate independently from one another but because of the shared object of critique, their actions amplify each other. As such, they underscore the links between violence suffered in the domestic sphere, urban public spaces, as well as in a manifold other locations such as the work place. In the third and final section, I return to the assembly as a physical gathering, arguing that a critical phenomenology of street protests should move beyond the concern with intercorporality to include attention to material objects.   Secondly, I show how they also presuppose passers-by that stop, read and respond to them. I suggest this interpellation should be understood as a moment of critique, in the sense in which critical phenomenologists (Guenther, Al-Saji, Salamon) have defined it as the suspension of everyday comportment and the exposure and contestation of historically contingent structures of oppression. Thirdly, I argue (contra Arendt) that protest does not always require the physical proximity of a group of people engaging in purposeful action-in-concert, but can also develop as a series (Sartre, Young), in this case, as the interpellation of passers-by as possible agents of social change, engaging in acts of indignant remembrance and of leaving women and other targeted groups alone. To summarize, these posters negotiate the limits to embodied resistance while granting visibility to those who are excluded or marginalized in public space.